Role of renal metabolism and excretion in 5-nitrofuran-induced uroepithelial cancer in the rat. - L A Spry; T V Zenser; S M Cohen; B B Davis (The Journal of Clinical Investigation, 1985)
5-Nitrofurans have been used in the study of chemical carcinogenesis. There is substantial evidence that N-[4-(5-nitro-2-furyl)-2-thiazolyl] formamide (FANFT) is deformylated to 2-amino-4-(5-nitro-2-furyl)thiazole (ANFT) in the process of FANFT-induced bladder cancer. Paradoxically, ANFT is less potent as a uroepithelial carcinogen than FANFT when fed to rats. Feeding aspirin with FANFT to rats decreases the incidence of bladder cancer. Isolated kidneys were perfused with 5-nitrofurans to determine renal clearances and whether aspirin acts to decrease urinary excretion of the carcinogen. In FANFT-perfused kidneys, FANFT was deformylated to ANFT and excreted (1.06 +/- 0.22 nmol/min) at a rate eightfold higher than excretion of FANFT. In kidneys perfused with equimolar ANFT, excretion of ANFT was 0.25 +/- 0.05 nmol/min, which suggests a coupling of renal deformylation of FANFT to excretion of ANFT in FANFT-perfused kidneys. Neither aspirin nor probenecid altered the urinary excretion or half-life of FANFT or ANFT. In rats fed 0.2% FANFT as part of their diet, coadministration of aspirin (0.5%) increased urinary excretion of ANFT during a 12-wk feeding study, which suggests decreased tissue binding or metabolism of ANFT. Kidney perfusion with acetylated ANFT (NFTA), a much less potent uroepithelial carcinogen, resulted in no ANFT excretion or accumulation, which indicates the specificity of renal deformylase. Renal deformylase activity was found in broken cell preparations of rat and human kidney. These data describe a unique renal metabolic/excretory coupling for these compounds that appears to explain the differential carcinogenic potential of the 5-nitrofurans tested. These results are consistent with the hypothesis that aspirin decreases activation of ANFT by inhibiting prostaglandin H synthase.